The uses of social networking applications and websites in promoting the gulf stock markets - Abdul Hadi, Alaa Makki; Almaeeni, Majid Saleh (ALBAHITH ALALAMI, 2023)
The study aims to identify the uses and the impact of social networking applications and websites on stock markets and their role in defining the details of dealing with stock movement and trading. The study also aims to highlight the role of these networks by increasing confidence in stock markets and companies as well as encouraging and inciting young people to invest in these markets, the study belongs to the descriptive analytical approach, the study population consisted of all current and potential investors in the stock and financial markets in the United Arab Emirates. The study used a questionnaire that was distributed to a number of followers of social networking pages and websites that deal with trading in stocks and stock exchanges. Among the 100 obtained 64 correct answers were obtained for the analysis of the study sample. among the most important findings of the study are those that showed that females lead in terms of the number of people using social networking applications and websites in promoting the Gulf and global stock markets, as they came in the first place with a greater percentage than the number of males, which is a clear indication of the interest of females in the process of trading shares and promoting through social networking apps and websites.